Symptomatic partial and transitional atrioventricular septal defect repaired in infancy. Issue 17 (28th December 2017) - Krupickova, Sylvia; Morgan, Gareth J; Cheang, Mun Hong; Rigby, Michael L; Franklin, Rodney C; Battista, Andrea; Spanaki, Ariana; Bonello, Beatrice; Ghez, Olivier; Anderson, David; Tsang, Victor; Michielon, Guido; et al.
Abstract : Objectives: Infants with symptomatic partial and transitional atrioventricular septal defect undergoing early surgical repair are thought to be at greater risk. However, the outcome and risk profile of this cohort of patients are poorly defined. The aim of this study was to investigate the outcome of symptomatic infants undergoing early repair and to identify risk factors which may predict mortality and reoperation. Methods: This multicentre study recruited 51 patients (24 female) in three tertiary centres between 2000 and 2015. The inclusion criteria were as follows: (1) partial and transitional atrioventricular septal defect, (2) heart failure unresponsive to treatment, (3) biventricular repair during the first year of life. Results: Median age at definitive surgery was 179 (range 0–357) days. Sixteen patients (31%) had unfavourable anatomy of the left atrioventricular valve: dysplastic (n=7), double orifice (n=3), severely deficient valve leaflets (n=1), hypoplastic left atrioventricular orifice and/or mural leaflet (n=3), short/poorly defined chords (n=2). There were three inhospital deaths (5.9%) after primary repair. Eleven patients (22%) were reoperated at a median interval of 40 days (4 days to 5.1 years) for severe left atrioventricular valve regurgitation and/or stenosis. One patient required mechanical replacement of the left atrioventricular valve. After median follow-up of 3.8 years (0.1–11.4 years), all patients were in New York Heart Association (NYHA) class I. In multivariable analysis, unfavourable anatomy of the left atrioventricular valve was the only risk factor associated with left atrioventricular valve reoperation. Conclusions: Although surgical repair is successful in the majority of the cases, patients with partial and transitional atrioventricular septal defect undergoing surgical repair during infancy experience significant morbidity and mortality. The reoperation rate is high with unfavourable left atrioventricular valve anatomy.